(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article examines the important role of geometry in the development of students’ logical thinking skills. Geometry is one of the fundamental branches of mathematics that helps learners improve reasoning, analytical thinking, problem-solving abilities, and spatial imagination. Through geometric concepts, theorems, and practical tasks, students learn to analyze information, compare shapes, draw conclusions, and justify their ideas logically.